TOE Framework for E-Commerce Adoption by MSMEs during The COVID-19 Pandemic: Can Trust Moderate? - Yoga Religia; Muhamad Ekhsan; Miftakul Huda; Anton Dwi Fitriyanto (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2023)
Currently, there are still many MSMEs in the regions that have not been connected to the digital ecosystem. This results in limited market reach, a lack of visibility, a lack of operational efficiency, and difficulty competing in the digital market. The purpose of this study is to review the adoption of e-commerce among MSMEs during the COVID-19 pandemic within the scope of the organization. Integrating the TOE framework (technology, organization, environment) with trust is carried out to explain the key parameters behind the adoption of e-commerce by MSMEs. This study collected samples using a saturated sample technique from 181 people who were members of the population. There were 153 questionnaires that were returned in full for further analysis using SEM-PLS modeling. The test results showed that technology did not have a significant influence on the adoption of e-commerce. Organizations, the environment during the pandemic, and trust have had a significant influence on the adoption of e-commerce. In addition, organizations that are moderated by trust have no significant effect on e-commerce adoption. The role of trust is as a moderation predictor. This research shows that the TOE framework is still strong enough to be used in explaining the adoption of e-commerce by MSMEs. This research also expands the TOE framework, where trust can also influence MSMEs to adopt e-commerce. Researchers and managers can use the set of variables that have been identified to strategize the adoption of e-commerce by MSMEs. This study presents a series of variables that can be used to study the adoption of e-commerce by MSMEs in the future.